2022
DOI: 10.3389/fimmu.2022.960001
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the SARS-CoV-2 infection and vaccination induced immune response in rheumatoid arthritis

Abstract: BackgroundTo investigate the factors that have significant impact on the Severe Acute Respiratory Syndrome Corona Virus 2 (SARS-CoV-2) infection and vaccination induced immune response in rheumatoid arthritis (RA).MethodsSerological response was measured by quantifying anti-SARS-CoV-2 specific antibodies, while the cell-mediated response was measured by a whole-blood test quantifying the interferon (IFN)-γ response to different SARS-CoV-2-specific domains.ResultsWe prospectively enrolled 109 RA patients and 43… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
18
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 32 publications
11
18
1
1
Order By: Relevance
“…We have also shown that the use of TNF inhibitors results in a significant attenuation of the humoral immune response. Our results are supported further by the work of Nemeth et al [ 31 ] in RA patients and Venerito et al [ 32 ] in patients with PsA.…”
Section: Discussionsupporting
confidence: 92%
“…We have also shown that the use of TNF inhibitors results in a significant attenuation of the humoral immune response. Our results are supported further by the work of Nemeth et al [ 31 ] in RA patients and Venerito et al [ 32 ] in patients with PsA.…”
Section: Discussionsupporting
confidence: 92%
“…However, the RA patient group had a lower proportion of participants with high antibody levels (NAT >90%) compared to the control group. A study conducted by Christensen et al [ 14 ] demonstrated a considerable decline in antibody levels within four months of the second vaccine dose in 41% of patients with immune-mediated inflammatory diseases, with a greater decline observed in patients receiving tumor necrosis factor (TNF)-alpha inhibitors, either as monotherapy or combination [ 15 ]. In our study, RA patients receiving a combination of three drugs showed low mean levels of anti-spike antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Whether patients with autoimmune rheumatic diseases (ARDs) are at increased risk for adverse COVID-19 outcomes due to the underlying chronic disease, or to the ongoing immunosuppressive treatments and comorbidities is still matter of debate (3,4). In addition, patients with ARDs have shown a reduced immunogenicity of anti-SARS-CoV-2 vaccines compared with healthy controls (5) especially if concomitantly treated with rituximab, abatacept, methotrexate, mycophenolate mofetil, or high doses of glucocorticoids. Administration of a booster dose of COVID-19 vaccine is, therefore, of particular importance in these patients to restore a protective antibody titre (5).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, patients with ARDs have shown a reduced immunogenicity of anti-SARS-CoV-2 vaccines compared with healthy controls (5) especially if concomitantly treated with rituximab, abatacept, methotrexate, mycophenolate mofetil, or high doses of glucocorticoids. Administration of a booster dose of COVID-19 vaccine is, therefore, of particular importance in these patients to restore a protective antibody titre (5).…”
Section: Introductionmentioning
confidence: 99%